Mapping of Occupations of the Populations in Urban Poor Areas - Laila Nagib (Journal of Indonesian Social Sciences and Humanities, 2011)
The goal of this study is to analyse and to map the occupations of the populations in the urban poor areas, and to analyse the welfare of workers in terms of several indicators of decent work. The study uses the ILO concept of decent work, which has four aspects (with 23 indicators): the rights of workers in the workplace; employment; social protection; and social dialogue. Our study used a combination of quantitative and qualitative methods, mainly surveys of households (sample size of 300) in two locations, Kelurahan Jamika (Bojongloa Kaler District) and Kelurahan Babakan Sari (Kiaracondong District).2 Those locations were chosen using the following criteria: population density, slum areas, poverty rates and variety of occupations. Qualitative methods were used to gather information, mainly through in-depth interviews and focus group discussions, and the data obtained were used to complement the quantitative data.